Logistical preconditions for economical reuse of end-of-life textiles - Ville Hinkka; Pirjo Heikkilä; Ali Harlin (Logistics 4.0 and Sustainable Supply Chain Management: Innovative Solutions for Logistics and Sustainable Supply Chain Management in the Context of Industry 4.0. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 26, 2018)
The importance of textile recycling has long been highlighted and extensively covered in the literature. More recently, tightening waste regulations have forced household waste management organizations to seriously consider different alternatives for reducing the amount of textiles in mixed waste. To date, the high logistical costs associated with collecting, sorting and treating of end-of-life (eol) textiles has prevented the use of recycled textiles in production. The particular challenges of organizing these operations cost-effectively include small batch size, material diversity, and complex sorting and treatment processes. Finding economical alternatives for the reverse logistics of eol textiles will help companies that use recycled textile materials in large-scale production to evolve. This paper addresses the issue through mixed methods research combining a quantitative and qualitative approach. The paper is based on a case study of organizing the eol textile ecosystem in Finland. The material was obtained primarily from interviews with stakeholders and workshops. The economic impacts of different alternatives are compared using a designed cost model. Based on the study, local collection of eol textiles should be carried out at regional level using the expertise of local municipal waste companies. Centralized sorting and treatment enables adequate volumes to justify investment in automation and paves the way for economies of scale benefits.
urn:nbn:de:gbv:830-88223582; 10419/209195; https://econpapers.repec.org/RePEc:zbw:hiclpr:26
Keywords: 650; Reverse logistics; Textiles; Recycling; Cost Model